2003
DOI: 10.1099/mic.0.26161-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional features of Rhodococcus ruber lipoarabinomannan

Abstract: The genus Rhodococcus is part of the phylogenetic group nocardioform actinomycetes, which also includes the genus Mycobacterium. Members of this phylogenetic group have a characteristic cell envelope structure, which is dominated by various complex lipids. Among these, lipoglycans are of particular interest since mycobacterial lipoarabinomannans are important immunomodulatory molecules that are likely to be involved in the subsequent fate of mycobacterial bacilli once inside phagocytic cells. Rhodococcus ruber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Consistently these macromolecules have been shown to consist of an MPI anchor unit and an (␣136) Manp core (18,20,22,39), although in some cases this can be quite short (21). However, there is evidently considerable variation in the nature of the substituting arabinan domains, varying from single t-Ara substituents in ReqLAM (18), RruLAM (22), and TotLAM (Fig. 5) to the more elaborate branched arabinan domain of AsuLAM (21) and the linear arabinan of TpaLAM (20).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistently these macromolecules have been shown to consist of an MPI anchor unit and an (␣136) Manp core (18,20,22,39), although in some cases this can be quite short (21). However, there is evidently considerable variation in the nature of the substituting arabinan domains, varying from single t-Ara substituents in ReqLAM (18), RruLAM (22), and TotLAM (Fig. 5) to the more elaborate branched arabinan domain of AsuLAM (21) and the linear arabinan of TpaLAM (20).…”
Section: Discussionmentioning
confidence: 96%
“…Actinomycete lipoglycans can be classified into a number of structural archetypes (54), of which the most extensively studied are the mycobacterial lipoarabinomannans (LAM) (6,7,39). LAM-like lipoglycans have also been identified in phylogenetically close relatives of the mycobacteria, which share common cell envelope features dominated by the presence of mycolic acids (13,52,55), and three lipoglycans from this taxon (the mycolata) have been recently characterized as structurally related members of a LAM family: ReqLAM from the equine pathogen Rhodococcus equi (18), RruLAM from Rhodococcus ruber (22), and TpaLAM from Tsukamurella paurometabola (20). Moreover, an additional representative of the LAM family (AsuLAM) has been characterized from the more distantly related actinomycete Amycolatopsis sulphurea (21), which lacks mycolic acids.…”
mentioning
confidence: 99%
“…In addition, position 3 of the myo-inositol was not acylated. Acylation of myo-inositol on lipoglycans actually seems to be re- stricted to the Mycobacterium genus, because it was not observed in any of the lipoglycans investigated so far arising from the genera, Rhodococcus (25,26), Tsukamurella (22), Amycolatopsis (28), or Turicella (30). These findings are surprising because acylation of myo-inositol was, at least, observed on PIM, in Rhodococcus equi (25).…”
Section: Maldi-tof/ms Analysis-maldi/msmentioning
confidence: 97%
“…Indeed, lipoglycans are not restricted to members of the mycobacteria, and a number of non-mycobacterial lipoglycans have been isolated and characterized in several actinomycete genera, including Rhodococcus (25,26), Gordonia (27), Amycolatopsis (28), Corynebacterium (29), and most recently Turicella (30) and Tsukamurella (22). In the latter study, we demonstrated that LAM from Tsukamurella paurometabola (TpaLAM) possesses a similar structural prototype when compared with mycobacterial LAM, with distinct mannan and arabinan domains, yet had weak biological activity (22); however, upon chemical degradation of the arabinan domain, the resulting lipomannan moiety elicited a powerful pro-inflammatory response as previously demonstrated with ManLAM (16).…”
mentioning
confidence: 99%
“…A number of non-mycobacterial actinomycetes possess lipoglycans, including Rhodococcus ruber (27), Rhodococcus equi (28), Amycolatopsis sulfurea (29), and Tsukamurella paurometabola. 3 Structurally, these lipoglycans are related to mycobacterial LAM, but are typically smaller in size.…”
mentioning
confidence: 99%